Relationship Between Wisdom, Aggression, Narcissism, and Self-Esteem Among University Students - Dr. Sajid Mahmood Alvi; Zainab Noor; Saba Bibi (Journal of Management Practices, Humanities and Social Sciences, 2022)
The present study investigated the relationship between adults' wisdom, aggression, narcissism, and self-esteem. A purposive sample (N = 300) of adults selected, both male and female, were included in the sample. Narcissism was measured through Narcissistic Personality Inventory (NPI) developed by Robert Raksin and Calvin. Wisdom is measured through Three Dimensional Wisdom Scale (3D-WS) developed by Monika Ardelt 2003. Aggression is measured through Buss and Perry Aggression Scale (BPAQ) developed by Buss and Perry. Self-esteem is measured through Rosen Berg Self-esteem Scale (RBSES) developed by Rosenberg. Descriptive statistics, alpha reliability, Pearson correlation, and t-test were computed to test the hypothesis. Pearson correlation showed a significant correlation between narcissism and self-esteem, the negative correlation of wisdom with aggression, and low self-esteem related to aggression but insignificantly, also a significant difference between wisdom on gender. This study helps mental health practitioners determine adults' overall psychological well-being.